Progress in ICP-MS Analysis of Minerals and Heavy Metals in Traditional Medicine - Chen, Wanyue; Yang, Yichu; Fu, Ke; Zhang, Dewei; Wang, Zhang (Frontiers in Pharmacology, 2022)
Aim: This study systematically reviewed the application of ICP-MS and its combined technology in the determination of mineral and heavy metal elements in medicinal materials derived from plants, animals, minerals and their preparations (Chinese patent medicine), and biological products. It provides a reference for improving the quality standard of traditional medicine and exploring the effective components, toxic components, and action mechanism of traditional medicine. Materials and Methods: A total of 234 articles related to the determination of mineral and heavy metal elements in medicinal materials derived from plants, animals, and minerals and their preparations (Chinese patent medicine) were collected from PubMed, CNKI, Web of Science, VIP, and other databases. They were classified and sorted by the inductively coupled plasma-mass-spectrometry (ICP-MS) method. Results: Of the 234 articles, 154 were about medicinal materials derived from plants, 15 about medicinal materials derived from animals, 9 about medicinal materials derived from minerals, 46 about Chinese patent medicine, 10 about combined technology application, and 3 about drugs being tested after entering the body. From the 154 articles on medicinal materials derived from plants, 76 elements, including Cu, Cd, Pb, As, Cr, Mn, and Hg, were determined, of which the determination of Cu was the most, with 129 articles. Medicinal materials derived from the roots, stems, leaves, flowers, and fruits and seeds of plants accounted for 25.97%, 18.18%, 7.14%, 7.79%, and 14.94%, respectively. Moreover, medicinal materials derived from the whole plants accounted for 14.94%, and other medicinal materials derived from plants and soil accounted for 11.04%. A total of 137 of the tested medicinal materials were from traditional Chinese medicine, accounting for 88.96%, 12 were from Arabic medicine (including Unani), accounting for 7.79%, 2 were from Tibetan medicine of China, and 1 was from Mongolian medicine of China, 1 was from Miao medicine of China, and 1 was from Zhuang medicine of China. In the 15 articles on medicinal materials derived from animals, 49 elements such as Cu, As, Cd, Hg, Se, Pb, and Mn were determined, of which Cu was the most. All the tested medicinal materials belong to traditional Chinese medicine. From the nine articles on medicinal materials derived from minerals, 70 elements such as Fe, Cu, Zn, Al, As, Se, and Na were determined, of which Fe, Cu, and Zn were the most. The tested medicinal materials all belong to traditional Chinese medicine. From the 46 articles on Chinese patent medicine, 62 elements such as Cu, As, Pb, Cd, Hg, Ni, and Cr were determined, of which Cu was the most. Regarding the tested Chinese patent medicine, 38 articles belong to traditional Chinese medicine, 6 to Tibetan medicine, and 2 to Mongolian medicine of China. Three articles determine the content of metal elements in biological samples such as animal hepatic venous blood, abdominal aortic blood, brain, liver, kidney, urine, and feces, and one article determines the content of metal elements in human lung and serum. From the 10 articles combined with liquid chromatography and gas chromatography, 16 elements such as MMA, DMA, AsIII, AsV, AsB, AsC, and AsI3 were determined, of which MMA and DMA were the most. It can realize elemental morphology and isotope analysis. The tested medicinal materials and Chinese patent medicine belong to traditional Chinese medicine. Conclusion: ICP-MS was applied the most in traditional Chinese medicine, followed by Arabic medicine. ICP-MS was used to determine more medicinal materials derived from plants, and Cu was determined the most. The characteristic inorganic element spectrum of medicinal materials can also be established. ICP-MS and its combined technology are widely used in Chinese patent medicine, but the test of biological samples is the least. The information provided in this article can provide a reference for improving the quality standard of traditional medicines and exploring the active ingredients and toxic ingredients and their mechanism of action.